IMPLEMENTATION OF PRODUCT PROMOTION STRATEGIES DURING THE COVID-19 PANDEMIC THROUGH DIGITAL MARKETING IN THE PURCHASE DECISION PROCESS - Riza M. Yunus (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2021)
The emergence of a pandemic causes the need for changes in marketing strategies. This is because, without any changes, the effectiveness of the usual marketing strategy will be significantly reduced. This study intends to determine how promotional methods are used in the purchasing decision process using digital marketing during the Covivirus-D19 pandemic. This research will employ a qualitative descriptive methodology. The data used in this study are derived from numerous research outcomes and earlier studies that are still relevant to this study's topic. The results of this study found that the changes made in changing the promotion strategy from conventional to digital were quite positive. The advantages are the practical nature of marketing, smaller operating expenses, and a faster response to consumers.